Autoimmunity to alpha myosin in a subset of patients with idiopathic dilated cardiomyopathy. Issue 6 (December 1995) - Goldman, J. H.; Keeling, P. J.; Warraich, R. S.; Baig, M. K.; Redwood, S. R.; Dalla Libera, L.; Sanderson, J. E.; Caforio, A. L.; McKenna, W. J.
Abstract : OBJECTIVE--To use an enzyme linked immunoassay (ELISA) technique to assess frequency and disease specificity of anti-alpha-myosin antibodies in patients with dilated cardiomyopathy and their relatives. METHODS--Evaluation was performed on sera (dilution 1/320) from 123 consecutive patients with dilated cardiomyopathy (WHO criteria) (age 42 (SD 14) years), 252 of their relatives (35 (17) years), 203 healthy controls (45 (16) years), and 92 patients with ischaemic heart disease (63 (11) years). RESULTS--Abnormal antibody levels were commoner in patients with dilated cardiomyopathy (25, 20%) than in ischaemic heart disease (4, 4%), or normal controls (4, 2%, P = 0.001). Forty one (16%) of the relatives had abnormal results compared to the controls (4, 2%, P < 0.001) and antibodies were detected in 20 (38%) of pedigrees. Relatives from non-familial kindreds had higher antibody levels than those with familial disease (P << 0.001), and higher antibody levels were identified in 53 relatives of probands who had abnormal results compared to 116 relatives for whom the proband had a normal result (0.37 (SEM 0.02) v 0.22 (0.01); P < 0.001). CONCLUSIONS--The finding of anti-alpha-myosin antibodies in 20% of patients with dilated cardiomyopathy, in 16% of their asymptomatic relatives, and in 38% of families (particularly those with non-familial disease and where proband also had an abnormal result) provides additional evidence for autoimmunity against alpha myosin in a subset of patients.